A fuzzy logic based classification for assessing of rock mass drillability. (20th February 2012) - Khalokakaie, Reza; Ataei, Mohammad; Mikaiel, Reza; Hoseinie, Seyed Hadi
This paper describes a fuzzy classification system for evaluating of rock mass drillability. Six parameters; Uniaxial Compressive Strength (UCS), joints dipping, Mohs hardness, joints aperture, joints spacing and grain size have been used. In this fuzzy system, each rock mass is classified into five modes from very poor to excellent condition. As a case study, 15 rock masses in two mines in Iran have been studied and classified using fuzzy system and classic classification. The comparison of the results shows that the fuzzy classification produces clearer results than classic system especially in rock masses with boundary condition.